2016
DOI: 10.1063/1.4966142
|View full text |Cite
|
Sign up to set email alerts
|

Phase coexistence in ferroelectric solid solutions: Formation of monoclinic phase with enhanced piezoelectricity

Abstract: Phase morphology and corresponding piezoelectricity in ferroelectric solid solutions were studied by using a phenomenological theory with the consideration of phase coexistence. Results have shown that phases with similar energy potentials can coexist, thus induce interfacial stresses which lead to the formation of adaptive monoclinic phases. A new tetragonal-like monoclinic to rhombohedral-like monoclinic phase transition was predicted in a shear stress state. Enhanced piezoelectricity can be achieved by mani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…For solid solutions ferroelectric monoclinic phases with enhanced piezoelectricity can be stabilized by internal strains [9] or long-range electrostatic interactions [10] caused by phase coexistence close to the morphotropic phase boundary. However, theoretical [11][12][13] and experimental studies [14][15][16] have revealed that formation of monoclinic phases can be achieved independently on the presence of a morphotropic phase boundary also via application of epitaxial lattice strain, in particular when the strain is anisotropic [11][12][13].…”
mentioning
confidence: 99%
“…For solid solutions ferroelectric monoclinic phases with enhanced piezoelectricity can be stabilized by internal strains [9] or long-range electrostatic interactions [10] caused by phase coexistence close to the morphotropic phase boundary. However, theoretical [11][12][13] and experimental studies [14][15][16] have revealed that formation of monoclinic phases can be achieved independently on the presence of a morphotropic phase boundary also via application of epitaxial lattice strain, in particular when the strain is anisotropic [11][12][13].…”
mentioning
confidence: 99%
“…3) 9,12,13,15 . The influence of the coexistence of different crystalline phases on the coercive electric field and the piezoelectric response have been reported for KNN and PZT systems 8,11,16,17,41 . Besides, only half of the voltage (+15 V) was required to reverse the polarization in the innermost area where the phase values are similar to those of the external area, as indication that the FE domains grow with the polarization pointing down in good agreement with the preferential growth orientations discussed above.…”
Section: Resultsmentioning
confidence: 99%
“…Our study shows that a ferroelectric-to-ferroelectric phase transition takes place in the broad temperature range from 180 • C to about 260 • C in which the ferroelectric room temperature and ferroelectric high temperature phases coexist. A coexistence of phases with different symmetries has also been observed in bulk piezoelectrics near the morphotropic phase boundary and has been shown to enhance the piezoelectric properties of the material [34,35]. The increased number of possible polarization orientations [34] and the flat energy profile enable polarization rotation [36], which is the widely accepted mechanism behind ultrahigh eletromechanical response at the morphotropic phase boundaries [37].…”
Section: Phase Transition Regimementioning
confidence: 93%